The Evolving Role of MicroRNAs in Endothelial Cell Dysfunction in Response to Infection - Watkin, Rebecca L.; Fitzpatrick, Glenn G.; Kerrigan, Steve W. (Seminars in Thrombosis and Hemostasis, 2018)
The microRNAs are short noncoding RNA molecules responsible for translational repression and silencing of target genes via binding to the mRNA. They are found in all eukaryotic cells and play a critical role in virtually all physiological processes, including within the cardiovascular system where they influence cellular development, differentiation, cardiovascular function, hemostasis, and programmed cell death. Dysregulated microRNA expression is associated with several conditions ranging from cancer and autoimmune disease to infection. Progressively, it has become increasingly clear that microRNAs are important components of the host response to microbes. The cardiovascular system, coupled with cells of the innate immune system, provide the initial interaction and first response to microbial infection, respectively. This review presents the current state of knowledge regarding the role of microRNAs with emphasis on their role in controlling endothelial cell function.
Keywords: vascular endothelial cell; microRNA; infection; sepsis